TAENIASIS PREVALENCE AND ASSOCIATED FACTORS IN BORRONG COMMUNE, DEMSA LGA, ADAMAWA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Taeniasis represents a human parasitic infection originating from three distinct tapeworm species: Taenia saginata, commonly known as the beef tapeworm, Taenia solium, referred to as the pork tapeworm, and Taenia asiatica, identified as the Asian tapeworm. The primary transmission of these parasitic organisms occurs when individuals consume poorly cooked meat, specifically raw or insufficiently cooked beef for T. saginata, or pork for both T. solium and T. asiatica. This research aims to understand how common a particular health issue is in the Borrong Community and explore what factors might be related to its occurrence in this specific area of Adamawa State, Nigeria. 376 people were picked by chance to participate in the research, which covers three villages: Borrong, Dilli, and Gwamba. Data analysis was conducted using SPSS Statistics Version 20. The 376 people studied, 129 were carriers of taeniasis infection with 34.3% infection rate. The highest infection occurred in age group 30-39 years in both males 18(51.4%) and females 16(43.3%), and is lower in ages 1-9 years in both males 1(11.1%) and females 1(9.1%). The source of water supply, hand washing habit after defecation, educational level, and pigs roaming freely, were significantly associated with taeniasis infections. Due to scarce feed resources, pigs in Africa are commonly allowed to move around freely, using waste as their primary food source. Increasing awareness about local risk factors such as pig management, education, and personal hygiene is crucial. This will play a great role in suppressing the taeniasis prevalence.
Keywords: Taeniasis; Infection; Tapeworm; Pigs; Risk factors